Medan as a Colonial Economic Nexus: The Legacy of Plantation Capitalism in the Early 20th Century - Annisa, Annisa; Br Sembiring, Madona; Sembiring, Jemima Regina Beru; Hadi, Satyo; Tanjung, Yushar (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This paper examines the emergence of Medan as a pivotal colonial economic hub in the early twentieth century, foregrounding the structural influence of plantation capitalism. Anchored in the broader trajectory of Dutch colonial expansion in Sumatra—especially in the Deli region—the study traces how large-scale plantation enterprises, predominantly in tobacco, rubber, and palm oil, fundamentally reshaped the city's urban morphology, socio-economic hierarchy, and administrative functions. The principal research inquiry centers on the role of plantation capitalism in engineering Medan’s economic configuration and entrenching colonial hierarchies. Employing a historical-analytical approach grounded in archival materials, colonial-era documentation, and academic literature, this study demonstrates that Medan’s accelerated urbanization and growing strategic importance were intrinsically linked to the imperatives of European capital and the systematic exploitation of both indigenous and migrant labor. The analysis further reveals that the spatial ordering of the city, investments in infrastructure, and patterns of social stratification were not merely coincidental, but deliberate outcomes of a capitalist logic institutionalized within the colonial apparatus. The findings suggest that Medan functioned not only as a logistical node in the transnational flows of commodities but also as a paradigmatic case of colonial urbanism shaped by plantation-driven accumulation. As such, the paper contributes to broader debates on the lasting imprint of colonial economic systems on Southeast Asia’s urban landscapes.